Data Collection in Care Homes for Older Adults: A National Survey in England - Barbara Hanratty; Arne Timon Wolters; Ann-Marie Towers; Karen Spilsbury; Julienne Meyer; Anne Killett; Liz Jones; Adam Gordon; Jennifer Kirsty Burton; Gizdem Akdur; Lisa Irvine; Krystal Warmoth; et al. (Journal of Long-Term Care, 2023)
Context: In many countries, there is a specification for information that should be collected by care homes. So-called ‘minimum data-sets’ (MDS) are often lengthy, and report on resident health and wellbeing, staff, and facilities. In the UK, the absence of any easily accessible data on the care home population was highlighted at the start of the COVID-19 pandemic. Care homes faced multiple requests for data from external agencies who had little knowledge of what care homes were already collecting.